Business process reengineering: A tutorial on the concept, evolution, method, technology and application - Grover, Varun; Malhotra, Manoj K (Journal of Operations Management, 1997)
AbstractIt is ironical that while much is being discussed about business process reengineering (BPR), most companies are still searching for methods to better manage radical change. Academics are studying the phenomenon but precious little has been published. Many basic questions remain unanswered. What does reengineering involve? Are there methods for effectively accomplishing BPR? Why is it so popular? Is there a logic behind reengineering? Is BPR fundamentally different from old Taylorian approaches to industrial engineering based on task decomposition and specialization? Is BPR the same as TQM, restructuring, etc.? What is the relationship between process redesign and organizational structures? How do we best plan, organize and control BPR efforts? Under what conditions will BPR be most effective? Answers to these questions are neither easy nor direct. However, this tutorial seeks to address them in a systematic, comprehensive and unbiased manner. In doing so, the tutorial will attempt to synthesize a variety of material from both practitioner and academic literature sources into a coherent précis that defines and discusses BPR in a language palatable to both the manager and the academic. A variety of frameworks will be presented to clarify the nature of the phenomenon as prescribed (in theory) and as companies are learning about it (in practice). The objective of this tutorial is to inform rather than provide an academic discourse.